2006
DOI: 10.3748/wjg.v12.i35.5692
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis C virus genotype 4 with peginterferon alfa-2a: Impact of bilharziasis and fibrosis stage

Abstract: PegIFN-alpha2a combined with ribavirin results in improvement in sustained response in HCV genotype 4, irrespective of history of bilharzial infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 28 publications
5
49
0
3
Order By: Relevance
“…This finding was similar to two studies (including 100 and 38 patients, respectively) using the alfa 2a form of pegylated interferon in genotype 4 patients and suggested that the response rates may be higher with Pegasys [16,17], as well as, In a study of Ribavirin in combination with either PEG-IFN alfa-2b or PEG-IFN alfa-2a for the treatment of chronic HCV infection, Ascione et al [18] reported a higher SVR rate with PEG-IFN alfa-2a than with PEG-IFN alfa-2b (68% versus 54.4%). However, any attempt at comparing treatment success between the two forms of pegylated interferons among this particular genotype would be unfair and premature, due to the lack of large, prospectively conducted studies using the Alfa 2a form of pegylated interferon [14].…”
Section: Discussionsupporting
confidence: 88%
“…This finding was similar to two studies (including 100 and 38 patients, respectively) using the alfa 2a form of pegylated interferon in genotype 4 patients and suggested that the response rates may be higher with Pegasys [16,17], as well as, In a study of Ribavirin in combination with either PEG-IFN alfa-2b or PEG-IFN alfa-2a for the treatment of chronic HCV infection, Ascione et al [18] reported a higher SVR rate with PEG-IFN alfa-2a than with PEG-IFN alfa-2b (68% versus 54.4%). However, any attempt at comparing treatment success between the two forms of pegylated interferons among this particular genotype would be unfair and premature, due to the lack of large, prospectively conducted studies using the Alfa 2a form of pegylated interferon [14].…”
Section: Discussionsupporting
confidence: 88%
“…With the introduction of pegylated IFN compounds in combination with ribavirin, the efficacy of treatment in HCV-4 further improved significantly. In various studies from European and Middle Eastern countries, SVR rates ranging from 43% to 70% were reported [39,40,53,[75][76][77][78][79][80][81][82][83][84][85][86][87][88]73,[89][90][91] (Table 1). These results are indeed higher than those (42-46%) achieved in genotype 1 patients but still lower than those (76-82%) reported in chronic hepatitis C genotype 2 and 3.…”
Section: Evolution Of Treatmentmentioning
confidence: 99%
“…Negative predictive factors at baseline include high viral load, presence of cirrhosis and steatosis, insulin resistance, IL-28B polymorphism TT, and HIV coinfection [75,86,73,[91][92][93]; these factors are associated with a lower SVR. A rather unexpected finding of the therapeutic trials in HCV-4 has been that under the same treatment regimen, patients from Egypt and the Middle East experienced higher SVR rates than patients from Europe or Africa.…”
Section: Evolution Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…De cualquier modo, la ausencia de RVP no parece justificar la interrupción del tratamiento. Derbala et al 25 Comparativa de la eficacia de pegIFN-a-2a frente a pegIFN-a-2b: los diferentes estudios que han comparado la respuesta a los 2 pegIFN, por lo general, no han logrado demostrar diferencias significativas en cuanto a la eficacia terapéutica. En el estudio realizado por Di Bisceglie et al en 2007 28 , se evaluaron ambos tratamientos en 380 pacientes de genotipo 1 y con alta carga vírica, y se mostró que la RVP en la semana 12 era menor en los pacientes tratados con pegIFN-a-2b (63% frente al 66%), aunque esta diferencia no fue estadísticamente significativa.…”
Section: Materials Y Métodosunclassified